Quantifying social performance: A review with implications for further work - Wild, Marcus G.; Cutler, Rebecca A.; Bachorowski, Jo-Anne (Frontiers in Psychology, 2023)
Human social performance has been a focus of theory and investigation for more than a century. Attempts to quantify social performance have focused on self-report and non-social performance measures grounded in intelligence-based theories. An expertise framework, when applied to individual differences in social interaction performance, offers novel insights and methods of quantification that could address limitations of prior approaches. The purposes of this review are threefold. First, to define the central concepts related to individual differences in social performance, with a particular focus on the intelligence-based framework that has dominated the field. Second, to make an argument for a revised conceptualization of individual differences in social-emotional performance as a social expertise. In support of this second aim, the putative components of a social-emotional expertise and the potential means for their assessment will be outlined. To end, the implications of an expertise-based conceptual framework for the application of computational modeling approaches in this area will be discussed. Taken together, expertise theory and computational modeling methods have the potential to advance quantitative assessment of social interaction performance.